GENDER SPECIFICS OF CLINICAL COURSE AND IN-PATIENT STAGE OF MANAGEMENT IN ST ELEVATION ACUTE CORONARY SYNDROME PATIENTS (BY THE RUSSIAN REGISTRY OF ACUTE CORONARY SYNDROME “RECORD-3”) - O. L. Barbarash; V. V. Kashtalap; I. S. Bykova; A. D. Erlikh А; N. A. Gratsiansky (Российский кардиологический журнал, 2017)
Aim. To evaluate gender differences in the disease course and in treatment at inpatient stage of management of ST elevation acute coronary syndrome (STEACS) patients by the data from the Russian Registry of Acute Coronary Syndromes “RECORD-3”.Material and methods. The study was conducted based on the data from Russian registry “RECORD-3”, in 47 institutions of 37 cities of Russia. The Registry included all consequtive patients with ACS, hospitalized in the participated institutions during march-april 2015, totally 2370 ACS patients. From the general group, patients were selected with the admission diagnosis STEACS (n=864). Mean age of STEACS patients was 62,6±12,4 y. Among them, 712 (82,4%) were primarily hospitalized into centers with invasive methods available, others (n=152, 17,6%) to non-invasive. The analysis was conducted, of the in-patient stage of patients, including reperfusion methods, and analysis of medication therapy.Results. More than a half of patients (68%) with STEACS were males, and hospitalized women were 10 years older. Females with ACS were at baseline clinically more complicated with arterial hypertension (AH), angina, chronic heart failure (CHF), diabetes 2 type, and atrial fibrillation in anamnesis. Higher number of acute heart failure was found (HF) (Killip II-IV) in females with ACS. There were no gender differences by the time of onset of pain to admittance and of doorballoon time. However coronary and ventriculography (CVG), percutaneous interventions (PCI), thrombolysis were done significantly (p=0,0001) rarer in females than in males. Higher mortality was found in females with STEACS comparing to males. There was higher rate of mortality in STEACS of females comparing to males (17,5% vs. 6,3%, p=0,0001). Monofactorial analysis revealed factors related to non-direction of patients to coronary arteriography: older age (more than 60 y. o.), female gender, cardiovascular comorbidity, acute heart failure at admittance. Conclusion. By the results of data analysis of “RECORD-3”, there were special characteristics of STEACS patients revealed for females: mean age is 10 years older than males; higher rate of cardiovascular comorbidity; reperfusion performed more rare, including outpatient stage of management. All these lead to significantly worse outcomes.